P-NE010. Spectrum of referrals to the ENMG laboratory of BNSRC, the apex Neuro Center in Brunei. Issue 8 (August 2021) - Sulaiman Bin Haji Sufardi, Muhammad; Nurauni Hamizah Binti Awang Mohd Ali, Dayang; Siti Noorazemah Binti Pengiran Ali, Dayangku; Nuraimi binti Saman, Siti; Deocareza Sabaricos, Jonly; Alexander, Mathew
Abstract : Introduction. Neuro-Electrophysiological (NEP) laboratories play an important role in precise characterisation, helping to guide treatment strategies and prognosticating neurological disorder. Brunei Neuroscience, Stroke Rehabilitation Centre (BNSRC) is the tertiary referral neurology centre for Brunei, a country in the South East Asian region with a population of 350, 000. The NEP lab does about 700-800 ENMG studies a year and tests were conducted using a Dantec Keypoint. The aim of this study is to examine the spectrum of referrals to the NEP lab of BNSRC from November 2018 to October 2019. Methods . Retrospective descriptive study. The referrals during the study period were retrieved from a computerised database and the records were reviewed. Results. There were a total of 688 referrals; 260 males, 428 females with a mean age of 49.1 years. The commonest referral was Mononeuropathies, predominantly Carpal Tunnel Syndrome at 53% (362) with Polyneuropathy at 12% (77) being the next common. Other mononeuropathies include Bell's Palsy, Ulnar Neuropathy, Peroneal Neuropathy and Radial Neuropathy made up 8% (55). Guillain-Barre Syndrome and Critical Illness Neuromyopathy made up 1.5% (10) and Myasthenia Gravis accounted for 4.6% (32) of referrals while Inflammatory Myopathies and Muscular Dystrophies accounted for 1.9% (13). Other referrals included conditions such as ALS, Spastic Paraparesis and Stiff Person Syndrome. Conclusion . ENMG Tests play a crucial role as they measure functional anatomy. This study captures the entire spectrum of disorders where the NEP laboratory helps guide the referral doctor. There is a need for protocol based studies, to learn newer techniques and to assist the Neurologist in EMG. The role of the NEP technologist is vital in getting technically robust recordings, even in less conducive surroundings like ICU and vital in developing a 'State of the Art' lab.